2014
DOI: 10.1039/c4ra06845a
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of poly(lactic acid)/halloysite nanocomposites by means of water assisted extrusion: structure, mechanical properties and fire performance

Abstract: This study shows the interest of elaborating polylactide/halloysite nanocomposites by means of water assisted extrusion (WAE). Besides, WAE gives access to materials with improved fire properties and prevents molecular degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 56 publications
2
44
1
Order By: Relevance
“…A similar decreasing trend is also manifested at 50% mass loss while increasing the HNT content appears to alleviate the reduction level of T 50% for both unmodified and modified HNT composite mats. The decrease of thermal stability at the above-mentioned two onset temperature levels is ascribed to the catalytic role of HNTs on the PLA pyrolysis with the existence of Si-OH and Al-OH acid sites on HNT external surfaces [48,49]. However, when the mass loss reaches 95%, T 95% values for composite mats conversely have monotonic increases with increasing the HNT content up to maximum 402.9 ºC and 420.8 ºC for 10 wt% HNT and modified HNT inclusions, respectively (T 95% = 370.0 ºC for PLA mats).…”
Section: Thermal Stabilitymentioning
confidence: 96%
“…A similar decreasing trend is also manifested at 50% mass loss while increasing the HNT content appears to alleviate the reduction level of T 50% for both unmodified and modified HNT composite mats. The decrease of thermal stability at the above-mentioned two onset temperature levels is ascribed to the catalytic role of HNTs on the PLA pyrolysis with the existence of Si-OH and Al-OH acid sites on HNT external surfaces [48,49]. However, when the mass loss reaches 95%, T 95% values for composite mats conversely have monotonic increases with increasing the HNT content up to maximum 402.9 ºC and 420.8 ºC for 10 wt% HNT and modified HNT inclusions, respectively (T 95% = 370.0 ºC for PLA mats).…”
Section: Thermal Stabilitymentioning
confidence: 96%
“…In another study, Prashantha et al [27] incorporated quaternary ammonium salt with benzoalkonium chloride treated HNTs into PLA in a high shear twin-screw extruder using masterbatch dilution process, showing improvements in the mechanical properties due to the better interfacial compatibility induced by the modification of the nanotube surface. Stoclet et al [28] compared the thermomechanical and flame retardant properties of PLA/HNTs nanocomposites prepared using a water-assisted extrusion process and conventional extrusion process. It was found that the injection of water into the polymer melt induced a better dispersion of the HNTs into the PLA matrix and also prevented polymer degradation during the extrusion due to a barrier effect of the water molecules that preferentially locate at the HNT-PLA interface.…”
Section: Introductionmentioning
confidence: 99%
“…They may work, however, also as potential flame retardants since they may be involved in the development of a thermal insulation layer on the surface of burning material during combustion. Such nanoparticles could be montmorillonite, expandable graphite, halloysite [51], bentonite, carbon nanotubes [52], and sepiolite [53]. Expandable graphite (EG) has low density, and it is non-burnable and capable of insulating the polymer substrate against radiant heat.…”
Section: Poly(lactic Acid) With Nanofiller As Flame Retardantmentioning
confidence: 99%
“…It was suggested that the formation of a char layer during combustion could be the reason for HRR reduction. Stoclet et al [51] produced PLA nanocomposites based on halloysite nanotube (HNT), using waterassisted extrusion. Water-assisted melt compounding of suitable nanofillers is a straightforward and safe method of producing nanocomposites [58].…”
Section: Poly(lactic Acid) With Nanofiller As Flame Retardantmentioning
confidence: 99%